Effects of Blood Flow Restricted Resistance Exercise on Recovery Blood Flow under Various Environmental Temperature Conditions - Yunbin Lee; Somang Son; Somi Yun; Yongsuk Seo; Dae Taek Lee (Asian Society of Kinesiology, 2024)
OBJECTIVES This study examines the impact of blood flow restriction (BFR) resistance exercise on blood flow across varying environmental temperatures, aiming to understand the physiological responses, exercise function, and recovery process affected by temperature changes. METHODS Seven healthy males (age: 26.4±1.7 years, weight: 72.7±6.8 kg, height: 174.5±2.0 cm) participated in biceps brachii exercises with and without BFR under low (10°C/25% humidity), moderate (25°C/50% humidity), and high (40°C/50% humidity) environmental conditions. Each participant completed six sessions of exercise across these conditions to assess the recovery phase blood flow changes. Blood flow measurements were taken during the recovery phase for analysis. RESULTS Blood flow significantly increased in high-temperature conditions, independent of BFR application, showing notable differences compared to low-temperature conditions (p<.05). CONCLUSIONS Environmental temperature significantly affects blood flow changes during BFR resistance exercise, with increased blood flow in high temperatures indicating a physiological adaptation to thermal stress. This suggests the need to consider environmental temperatures in optimizing BFR exercise protocols.